2005
DOI: 10.1007/s11136-004-3507-7
|View full text |Cite
|
Sign up to set email alerts
|

Nature and correlates of SF-12 physical and mental quality of life components among low-income HIV adults using an HIV service center

Abstract: HRQOL in this sample of low-income HIV adults was comparable to other HIV populations. Identifying strategies for increasing social support and medication adherence for economically disadvantaged persons with HIV/ AIDS may improve their HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 40 publications
4
17
1
1
Order By: Relevance
“…Consistent with the literature, this study did not find any of the selected demographic factors (i.e., income, gender, sexual orientation, race) to be associated with HRQoL. 22,56,57 Furthermore, this study replicated the association between HIV symptoms 4,20,57 and perceived stress 58,59 and diminished HRQoL, as well as perceived availability of social support 4,25 and improved HRQoL. This study also found that HIVrelated stress was a significant predictor of emotional well-being/living with HIV, but not overall HRQoL or other domains of HRQoL.…”
Section: Persons Et Alsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with the literature, this study did not find any of the selected demographic factors (i.e., income, gender, sexual orientation, race) to be associated with HRQoL. 22,56,57 Furthermore, this study replicated the association between HIV symptoms 4,20,57 and perceived stress 58,59 and diminished HRQoL, as well as perceived availability of social support 4,25 and improved HRQoL. This study also found that HIVrelated stress was a significant predictor of emotional well-being/living with HIV, but not overall HRQoL or other domains of HRQoL.…”
Section: Persons Et Alsupporting
confidence: 87%
“…21,23,24 Additionally, a number of psychosocial factors, including social support, coping skills, perceived stress, grief, and psychological distress, have been found to predict HRQoL. 2,4,25,26 Finally, HIV-related stigma and discrimination have been shown to have a negative impact on HRQoL, 20,23,27,28 above and beyond even the severity of HIV symptoms and depression. 20 While numerous studies have examined the impact of clinical, demographic, and psychosocial factors, including HIV-related stigma, on HRQoL, research on the association between shame and HRQoL is notably absent from the literature.…”
mentioning
confidence: 99%
“…In terms of demographic characteristics, several factors have been identified: (a) older age results in lower HRQOL scores (Campsmith, Nakashima, & Davidson, 2003;Logie & Gadalla, 2009); (b) lower income negatively correlates with HRQOL (Campsmith et al, 2003;Logie & Gadalla, 2009); (c) ethnic minorities compared with non-Hispanic Whites have lower HRQOL (Campsmith et al, 2003); (d) formal education is positively related to HRQOL (Campsmith et al, 2003); and (e) people with unstable, temporary, or no employment have lower HRQOL scores compared with those with stable employment (Viswanathan et al, 2005). In terms of biomedical characteristics, the following variables have been identified: (a) CD4 is negatively associated with HRQOL (Campsmith et al, 2003;Jia et al, 2005), but also that the relation between CD4 and HRQOL varies over time (Jia et al, 2007); and (b) medication adherence is positively associated with HRQOL (Viswanathan et al, 2005).…”
Section: Quality Of Life and Social Support And Social Underminingmentioning
confidence: 99%
“…Identification of these correlates can help researchers, providers, and patients identify the most effective points of intervention in the health delivery process. One such correlate is social support; social support has been found to be related positively to HRQOL for PLWH (Jia et al, 2007;Viswanathan, Anderson, & Thomas, 2005).…”
mentioning
confidence: 99%
“…Internal consistency reliability measured by Crohnbach a had a value of 0.86 for the English version of MMAS (personal communication, Morisky 2002), which is superior to the Morisky-Green test, which has a Crohnbach a value of 0.61 [21]. MMAS has previously been used to measure adherence to antiretroviral treatment [22]. Respondents scoring 11 or above in the MMAS summary score were classified as adherent (scale ranging 1-13).…”
Section: Morisky Medication Adherence Scale In 2002mentioning
confidence: 99%